Acridinium‐conjugated aromatic heterocycles as highly potent FtsZ inhibitors: Design, synthesis, and biological evaluation. Issue 6 (10th March 2022) - Song, Di; Zhang, Nan; Ma, Yangchun; Zhang, Shenyan; Chen, Weijin; Guo, Ting; Ma, Shutao
Abstract: The epidemic of multidrug resistance (MDR) is a serious threat to public health, and new classes of antibiotics with novel mechanisms of action are in critical need. We rationally designed and efficiently synthesized three series of new chemical entities with potential antibacterial activity targeting filamenting temperature‐sensitive mutant Z (FtsZ). Evaluation of these compounds against a panel of Gram‐positive bacteria including MDR and vancomycin‐resistant Enterococcus  strains indicated that most compounds showed enhanced antibacterial efficacy, comparable or even superior to the reference drugs. The newly synthesized compounds proved to be substrates of the Escherichia coli efflux pump AcrB, thus affecting the activity. Their structure–activity relationships were summarized in detail. The most potent compound 10f quickly eliminated bacteria in a bactericidal mode, with low susceptibility to induce bacterial resistance. Further mechanistic studies with the Bs FtsZ protein revealed that 10f functioned as an effective FtsZ inhibitor through altering the dynamics of FtsZ self‐polymerization via a stimulatory mechanism, which leads to inhibition of cell division and cell death. Besides, 10f not only displayed no obvious cytotoxicity to mammalian cells but also had a high efficacy in a murine model of bacteremia in vivo. Regarded as a whole, our findings highlight 10f as a promising new FtsZ‐targeting bactericidal agent. Abstract : To overcome the epidemic of multidrug resistance, a series of new acridinium‐conjugated aromatic heterocycles derivatives were designed via molecular hybrid strategy. Compound 10f showed a broad antibacterial spectrum and high potency against Gram‐positive and ‐negative bacteria, including methicillin‐resistant Staphylococcus aureus and vancomycin‐resistant Enterococcus strains, and turned out to be a new filamenting temperature‐sensitive mutant Z‐targeting bactericidal agent.